First report of a pseudorabies virus in porcupines: Genomic characterization of a recombinant strain and safety assessment of the Bartha-K61 vaccine - Nana Yan; Jingru Xu; Lin Zheng; Sisi Fan; Hui Guo; Yue Qi; Xinling Lai; Yaoming You; Kaixin Zhang; Jingxue Liu; Jiankui Liu; Ailing Dai; et al. (Veterinary Microbiology, 2026)

Characterization of the pathogenicity of newly emerged NADC30-Like PRRSV strains causing severe brain infections via twice inter-lineage recombination - Yuan Yang; Cheng Luo; Yixue Yan; Haoyu Chen; Feimin Xie; Ziyi Wang; Wei Wei; Mingsheng Cen; Xinyue Chen; Wenlin Huang; Xin Lan; Yu Feng; et al. (Veterinary Microbiology, 2026)

Rapid evolution of life history of two water fleas in response to inter-specific competition - Jiasheng Yang; Jianan Li; Ailing Yan; Haoran Zhang; Qianqian Wei; Xiaodong Jiang (Journal of Oceanology and Limnology, 2026)

How obesity and overweight affect the carbon footprint of China's healthcare: A dire situation calling for urgent action - Zhimin Shi; Lixiao Zhang; Pengpeng Zhang; Yan Hao; Xin Xiong; Xinqing Li; Ailing Liu (Environmental Impact Assessment Review, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Dynamics and correlations of maximum water age zones and nutrients in the Changjiang Estuary, China - Yanliang Du; Xiaoyu Ma; Guiquan Xu; Xiaobo Liu; Chang Liu; Shiyan Wang; Shiqiang Lu; Zhen Han; Ailing Yan; Xu Ma (Estuarine, Coastal and Shelf Science, 2024)

Pasteurized Akkermansia muciniphila mitigates 5-FU-induced intestinal mucositis in tumor-bearing mice through suppression of the cGAS-STING pathway and epithelial cell apoptosis - Yue Teng; Jiahui Li; Chunhong Yan; Ailing Wang; Xiaomeng Ren; Xiaodong Xia (Food Bioscience, 2024)

Pasteurized Akkermansia muciniphila improves immunity and relieves other toxic effects in 5-fluorouracil treated BALB/c mice - Yue Teng; Dongyun Zhao; Chunhong Yan; Xiaomeng Ren; Ailing Wang; Xiaodong Xia (Food Bioscience, 2024)

Triassic oceanic–continental transition of the Ganzi–Litang Ocean basin: Evidence from high-Mg andesites and Nb-enriched basalts in the Litang area, Eastern Tibet - Songtao Yan; Ailing Ding; Xuejian Dai; Tao Liu; Hu Li; Hongrui Dai; Peng Chen; Qingsong Wu; Lidong Zhu (Journal of Asian Earth Sciences, 2024)

Metabolomic and transcriptomic integrated analysis revealed the decrease of monoterpenes accumulation in table grapes during long time low temperature storage - Huiling Wang; Xiaoyue Wang; Ailing Yan; Zhenhua Liu; Jiancheng Ren; Haiying Xu; Lei Sun (Food Research International, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Effects of Cadmium on Kidney Function of the Freshwater Turtles Mauremys reevesii - Aiguo Dong; Huidong Dong; Hui He; Ailing Dong; Juanjuan Yan; Junfeng Huo (Biological Trace Element Research, 2023)

Lipopolysaccharide induces inflammatory microglial activation through CD147-mediated matrix metalloproteinase expression - Chunyan Yao; Xiaoling Liu; Yan Tang; Chunmei Wang; Chenggang Duan; Xiaoyan Liu; Mingliang Chen; Yumeng Zhou; Enjie Tang; Ying Xiang; Yafei Li; Ailing Ji; et al. (Environmental Science and Pollution Research, 2022)

Lipid peroxidation of kidney of the turtle Mauremys reevesii caused by cadmium - Aiguo Dong; Junfeng Huo; Juanjuan Yan; Ailing Dong; Biwang Liu (Environmental Science and Pollution Research, 2021)

Oxidative stress in liver of turtle Mauremys reevesii caused by cadmium - Aiguo Dong; Junfeng Huo; Juanjuan Yan; Ailing Dong (Environmental Science and Pollution Research, 2021)

Effects of cadmium on the activities of ALT and AST as well as the content of TP in plasma of freshwater turtle Mauremys reevesii - Junfeng Huo; Aiguo Dong; Juanjuan Yan; Ailing Dong (Environmental Science and Pollution Research, 2020)

Effects of cadmium on the gene transcription of the liver in the freshwater turtle (Chinemys reevesii) - Junfeng Huo; Aiguo Dong; Juanjuan Yan; Ailing Dong (Environmental Science and Pollution Research, 2020)

MiR-126-3p promotes the cell proliferation and inhibits the cell apoptosis by targeting TSC1 in the porcine granulosa cells - Xiaolong Yuan; Xi Deng; Xiaofeng Zhou; Ailing Zhang; Yan Xing; Zhe Zhang; Hao Zhang; Jiaqi Li (In Vitro Cellular & Developmental Biology - Animal, 2018)

Engineering low phorbol ester Jatropha curcas seed by intercepting casbene biosynthesis - Chunhong Li; Ailing Ng; Lifen Xie; Huizhu Mao; Chengxiang Qiu; Ramachandran Srinivasan; Zhongchao Yin; Yan Hong (Plant Cell Reports, 2016)

Microarray data uncover the genome-wide gene expression patterns in response to heat stress in rice post-meiosis panicle - Xianwen Zhang; Hairong Xiong; Ailing Liu; Xiaoyun Zhou; Yan Peng; Zhuoxue Li; Guangyu Luo; Xiangrong Tian; Xinbo Chen (Journal of Plant Biology, 2014)

Overexpression of Transcription Factor OsWR2 Regulates Wax and Cutin Biosynthesis in Rice and Enhances its Tolerance to Water Deficit - Xiaoyun Zhou; Matthew A. Jenks; Juan Liu; Ailing Liu; Xiangwen Zhang; Jianhua Xiang; Jie Zou; Yan Peng; Xinbo Chen (Plant Molecular Biology Reporter, 2014)

Complete nucleotide sequence of a norovirus GII.4 genotype: evidence for the spread of the newly emerged pandemic Sydney 2012 strain to China - Yuqi Huo; Ailing Cai; Hui Yang; Mingli Zhou; Jiaxin Yan; Dingxiang Liu; Shuo Shen (Virus Genes, 2014)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)